2009
DOI: 10.1177/070674370905400409
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Metabolic Risk Profile under Second-Generation Antipsychotics: A Pilot Intervention Study

Abstract: Objective:To assess the impact of a weight management program on metabolic health of second-generation antipsychotic (SGA)-treated patients.Methods: A prospective 12-week intervention program including individual exercise training and nutritional group sessions was performed as a pilot study. An intervention group of 6 SGA-treated patients (5 men and 1 woman; mean 15.0, SD 11.8 months) was compared with 10 reference patients under SGAs (8 men and 2 women; mean 14.0, SD 14.2 months), presenting similar age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
(18 reference statements)
1
14
0
1
Order By: Relevance
“…Studies on patients with schizophrenia have usually investigated low-intensity exercise corresponding to <70% peak heart rate (HR peak ) (14-17). Only a few studies have applied direct measurements of oxygen uptake (18-20), but the exact level of VO 2peak are not described.…”
mentioning
confidence: 99%
“…Studies on patients with schizophrenia have usually investigated low-intensity exercise corresponding to <70% peak heart rate (HR peak ) (14-17). Only a few studies have applied direct measurements of oxygen uptake (18-20), but the exact level of VO 2peak are not described.…”
mentioning
confidence: 99%
“…19 In total, 12 interventions were included as one study utilized two separate intervention groups. 19 The majority of the interventions were delivered over 12 weeks, 14,[17][18][19]21,22 with the longest intervention spanning 18 months. 13 The range of weekly sessions was 0-3.…”
Section: Resultsmentioning
confidence: 99%
“…19 Four of the identified studies stated that university-trained kinesiologists or exercise physiologists supervised the interventions. 14,16,21,22 Five studies (45%) assessed aerobic capacity (VO2 max or VO2 peak) 16,17,19,21,22 as an outcome measure whereas four studies assessed self-reported physical activity, predominantly using the International Physical Activity Questionnaire-Short Form. 14,[20][21][22]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos anteriores revelam que a participação em programas de AF regular possibilita aos indivíduos com esquizofrenia diminuir o peso (5,7,19,43) , o índice de massa corporal (5-7, 19, 43) , e a circunferência da cintura (43) , bem como, melhorar a capacidade funcional para o exercício (38) , a capacidade cardiorrespiratória (6,42) , determinadas variáveis psicológicas (e.g., autoestima, controlo emocional, funções sociais) (10,21,42) e a qualidade de vida (1,21,27) . Julgamos que o nosso estudo, apesar de se tratar de um estudo piloto com algumas limitações metodológicas, poderá contribuir para um melhor entendimento da importância da AF na DM de indivíduos com esquizofrenia.…”
Section: A Avaliação Da Preferência Manual (Pm) Dos Participantes Foiunclassified